The Politics of Multicultural Citizenship: Problems, Challenges and Prospects of Civil Religion Institutionalization in Indonesia - Masdar Hilmy (JICSA : Journal of Islamic Civilization in Southeast Asian, 2016)
This paper analyzes how the issue of multicultural citizenship and civil religion has been practiced and debated in Indonesia from political perspective. The writer argues that multicultural citizenship is closely associated with civil religion, in the sense that the latter is the way to objectify and strengthen the earlier. The problem is that the more civil religion is routinized and objectified in daily life, the less the sense of the sacred is. As soon as religion has widely been practiced by members of the society, it soon becomes secular, losing its religious sense since it entangles with local culture. Therefore, objectifying and mainstreaming civic religion must be accompanied by keeping its religious arguments in order to give the civil religion sense of the sacred. As a multicultural country, Indonesia has long acknowledged multicultural citizenship. Sociologically speaking, each Indonesian citizen can live side by side regardless his/her socio-religious background without any discrimination. Indonesian constitution (UUD 1945) clearly states that everyone is equal before the law. Nevertheless, Indonesia’s multicultural citizenship soon becomes at stake, especially when political and economic factors interfere into the public sphere.